Rainfall - runoff modelling in the Bharathapuzha river basin - AJI R; Jayakrishnan B. V; Najash Babu K; Er. Vishnu B (Guide) (Tavanur 1999 Department of Irrigation and Drainage Engineering)
Rainfall - runoff modelling in the Bharathapuzha river basin
Rainfall - runoff modelling in the Bharathapuzha river basin